An introduction to fluid mechanics - Morrison, Faith A. (Cambridge ; New York : Cambridge University Press, 2012)
"Why Study Fluid Mechanics? 1.1 Getting Motivated Flows are beautiful and complex. A swollen creek tumbles over rocks and through crevasses, swirling and foaming. A child plays with sticky tafy, stretching and reshaping the candy as she pulls it and twist it in various ways. Both the water and the tafy are fluids, and their motions are governed by the laws of nature. Our goal is to introduce the reader to the analysis of flows using the laws of physics and the language of mathematics. On mastering this material, the reader becomes able to harness flow to practical ends or to create beauty through fluid design. In this text we delve deeply into the mathematical analysis of flows, but before beginning, it is reasonable to ask if it is necessary to make this significant mathematical effort. After all, we can appreciate a flowing stream without understanding why it behaves as it does. We can also operate machines that rely on fluid behavior - drive a car for exam- 15 behavior? mathematical analysis. ple - without understanding the fluid dynamics of the engine, and we can even repair and maintain engines, piping networks, and other complex systems without having studied the mathematics of flow What is the purpose, then, of learning to mathematically describe fluid The answer to this question is quite practical: knowing the patterns fluids form and why they are formed, and knowing the stresses fluids generate and why they are generated is essential to designing and optimizing modern systems and devices. While the ancients designed wells and irrigation systems without calculations, we can avoid the wastefulness and tediousness of the trial-and-error process by using mathematical models"--